Activities of the Japanese Arctic Glaciological Expedetion in 1999 (JAGE 1999) (report) - Motoyama, Hideaki; Watanabe, Okitsugu; Goto-Azuma, Kumiko; Igarashi, Makoto; Miyahara, Morihiro; Nagasaki, Tomoharu; Karloef, Lars; Isaksson, Elisabeth (2001)
P(論文) To reconstruct climatic and environmental changes in Svalbard in the past several hundred years, an ice core was drilled on the summit of Austfonna ice cap, Svalbard (79°50′N, 24°00′E, 750m a. s. l.) to a depth of 289m in May 1999 by a Japan-Norway cooperative project. Ice core stratigraphy measurement, digital camera recording of the ice core, and measurements of bulk density and electrical conductivity of ice (ECM) were conducted in situ. Snow pit observations were carried out at three different sites. Fresh falling snow, drifting snow and surface hoar were sampled. departmental bulletin paper